(untitled) - Hoover, John (New Jersey, 2006)
The defining characteristic in an idiot is cluelessness. The challenge for sales professionals is to surgically implant enough of a clue in their idiot customers to reach the correct buying decision. The problem comes when salespeople forget that they have inner idiots, too._ True sales professionals work to ensure their own clues are intact. The critical path to selling to the clueless is a 12-stage process.
Keywords: Selling,Sự bán hàng; Psychological aspects,Khía cạnh tâm lý